Genotyping of clinical and environmental multidrug resistant Enterococcus faecium strains - Shokoohizadeh, Leili; Mobarez, Ashraf; Alebouyeh, Masoud; Zali, Mohammad; Ranjbar, Reza (Indian journal of pathology & microbiology, 2017)
Context: Multidrug resistant (MDR) Enterococcus faecium is a nosocomial pathogen and clonal complex 17 (CC17) is the main genetic subpopulation of E. faecium in hospitals worldwide. Aims: There has thus far been no report of major E. faecium clones in Iranian hospitals. Subjects and Methods: The present study analyzed strains of MDR E. faecium obtained from patients and the Intensive Care Unit environments using pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) to determine the antibiotic resistance patterns and genetic features of the dominant. Results: clones of E. faecium. PFGE and MLST analysis revealed the presence of 17and 15 different subtypes, respectively. Of these, 18 (86%) isolates belonged toCC17. Most strains in this clonal complex harbored the esp gene and exhibited resistance to vancomycin, teicoplanin, ampicillin, ciprofloxacin, gentamicin, and erythromycin. The MLST results revealed 12 new sequence types (ST) for the first time. Approximately 50% of the STs were associated with ST203. Conclusion: Detection of E. faecium strains belonging to CC17 on medical equipment and in clinical specimens verified the circulation of high-risk MDR clones among the patients and in hospital environments in Iran.